2014
DOI: 10.1891/2156-5287.4.2.69
|View full text |Cite
|
Sign up to set email alerts
|

A Situational Analysis of the Status of Midwifery in North Africa and the Middle East

Abstract: Midwives from the Middle East and North African (MENA) region convened in Dubai, United Arab Emirates in 2012 to engage for the first time ever in a discussion concerning regional strategic interventions to strengthen midwifery and the work of midwives in the Arab countries. The workshop was an opportunity to establish a culture of positive and balanced collaboration and mutual understanding among midwives and between midwives and other maternity care professionals including nurses and obstetricians. Key chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Making midwifery related higher education accessible in Africa, provides a pathway by which to increase availability of skilled midwives trained to ICM standards 24 . The integration of midwifery programs of study within degree-granting pathways, such as the LMD level, has been perceived in Europe 25 , some Africa and Middle-East countries 14 as a reform that offers midwives the opportunity of academic advancement and may pave the way to career progression. Nevertheless, it has to be determined which terminology is needed to distinguish the different educational levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Making midwifery related higher education accessible in Africa, provides a pathway by which to increase availability of skilled midwives trained to ICM standards 24 . The integration of midwifery programs of study within degree-granting pathways, such as the LMD level, has been perceived in Europe 25 , some Africa and Middle-East countries 14 as a reform that offers midwives the opportunity of academic advancement and may pave the way to career progression. Nevertheless, it has to be determined which terminology is needed to distinguish the different educational levels.…”
Section: Discussionmentioning
confidence: 99%
“…In several African countries, the fundamental issue faced by midwives is their unclear identity buried among a multitude of health workers educated and employed as midwives who do not meet the International Definition of the Midwife of the ICM (International Confederation of Midwives) 13 . In several African countries midwifery, la pratique de sage-femme, is carried out by different health professionals such as obstetricians, general practitioners, nurses, registered and community midwives, community health extension workers, and often traditional birth attendants 2,14 . There is no specific regulatory body for midwives in some African countries and midwifery is not legally classified as an autonomous profession in many 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, it is suggested that medicalization of birth limits midwifery autonomy (Ghérissi & Brown, 2014). Therefore, infrastructure and culture at work impacts on autonomy in midwifery practice (Zolkefli et al, 2020), while collegial relationships could support or hinder midwives' autonomy (Clemons et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Today, the improved quality of midwifery services is one of the major international controversies, and among healthcare providers, midwives play substantial roles in maintaining and improving the health of mothers and children at three levels of health and treatment centers, family and society (11). Midwives in developing countries face numerous challenges in the areas of education, laws, lack of autonomous professional associations, and management and support issues (12). The most fundamental problem is midwives' unclear identity and job duties, which sometimes, because of reasons such as lack of job planning and inappropriate service conditions including salaries, rewards and educational bene ts, not only prevent their professional progress, but also leads to job burnout caused by working in uncertain conditions, insecure workplace and lack of appropriate reference system (12).…”
Section: Introductionmentioning
confidence: 99%
“…Midwives in developing countries face numerous challenges in the areas of education, laws, lack of autonomous professional associations, and management and support issues (12). The most fundamental problem is midwives' unclear identity and job duties, which sometimes, because of reasons such as lack of job planning and inappropriate service conditions including salaries, rewards and educational bene ts, not only prevent their professional progress, but also leads to job burnout caused by working in uncertain conditions, insecure workplace and lack of appropriate reference system (12). By contrast, many developed countries, by formulating community-based policies, provide opportunities for midwives to strengthen their skills in organizing and directing local services for women and families (13).…”
Section: Introductionmentioning
confidence: 99%